Online bill payment system - Konreddy, Venkata Sri Vatsav Reddy (Kansas State University, 2009)
Keeping track of paper bills is always difficult and there is always a chance of missing bill payment dates. Online Bill Payment application is an interactive, effective and secure website designed for customers to manage all their bills. The main objective of this application is to help customers to receive, view and pay all the bills from one personalized, secure website there by eliminating the need of paper bills. Once customers register in the website, they can add various company accounts. The information is verified with the company and the accounts are added. After the customers add the company accounts they can receive notifications about new bills, payments and payment reminders. All the information dealing with sensitive data is passed through a Secure Socket Layer for the sake of security. This website follows MVC architecture. Struts is used to develop the application. Well established and well proven design patterns like Business Delegate, Data Access Object, and Transfer Object are used to simplify the maintenance of the application. For the communication between the website and companies, web services are used. Apache Axis2 serves as the web services container and Apache Rampart is used to secure the information flow between the web services. Tiles, JSP, HTML, CSS and JavaScript are used to provide a rich user interface. A part from these, Java Mail is used to send emails and concepts like one way hashing, certificates, key store’s, and encryption are implemented for the sake of security. The overall system is tested using unit testing, manual testing and performance testing techniques. Automated test cases are written whenever possible to ensure correctness of the functions. Manual testing further ensures that the application is working as expected. The system is subjected to different loads and the corresponding behavior is observed at different loads. The unit and manual testing revealed that the functionality of each module in the system is behaving as expected for both valid and invalid inputs. Performance testing revealed that the website works fine even when the server is subjected to huge loads.
Keywords: J2EE; Struts; Design pattern; SSL; Computer Science (0984)